Misoprostol-induced pulmonary edema in a parturient with postpartum cardiomyopathy - Bikash Ranjan Ray; Puneet Khanna; Vimi Rewari; Renu Sinha; Ajisha Aravindan; Anjan Trikha (Wolters Kluwer Medknow Publications, 2011)
Misoprostol, a synthetic prostaglandin E1 (PGE1) analogue, although not the first-line drug in the management of postpartum hemorrhage, is frequently used for this purpose due to its safety profile and cost-effectiveness. Cardio-pulmonary complications have been previously reported with use of prostaglandin analogues but not with misoprostol. We describe a case of pulmonary edema after the use of vaginal misoprostol for treatment of postpartum vaginal bleed in an otherwise healthy asymptomatic patient, who was later diagnosed as a case of peripartum cardiomyopathy.